Historical biogeography, systematics, and integrative taxonomy of the non-Ethiopian speckled pelage brush-furred rats (Lophuromys flavopunctatus group) - Onditi, Kenneth Otieno; Demos, Terrence C; Kerbis Peterhans, Julian; Chen, Zhong-Zheng; Bryja, Josef; Lavrenchenko, Leonid A; Musila, Simon; Verheyen, Erik; Van de Perre, Frederik; Akaibe, Benjamin Dudu; de la Sancha, Noé U; Jiang, Xue-Long (BMC ecology and evolution, 2021)
BACKGROUND: The speckled-pelage brush-furred rats (Lophuromys flavopunctatus group) have been difficult to define given conflicting genetic, morphological, and distributional records that combine to obscure meaningful accounts of its taxonomic diversity and evolution. In this study, we inferred the systematics, phylogeography, and evolutionary history of the L. flavopunctatus group using maximum likelihood and Bayesian phylogenetic inference, divergence times, historical biogeographic reconstruction, and morphometric discriminant tests. We compiled comprehensive datasets of three loci (two mitochondrial [mtDNA] and one nuclear) and two morphometric datasets (linear and geometric) from across the known range of the genus Lophuromys. RESULTS: The mtDNA phylogeny supported the division of the genus Lophuromys into three primary groups with nearly equidistant pairwise differentiation: one group corresponding to the subgenus Kivumys (Kivumys group) and two groups corresponding to the subgenus Lophuromys (L. sikapusi group and L. flavopunctatus group). The L. flavopunctatus group comprised the speckled-pelage brush-furred Lophuromys endemic to Ethiopia (Ethiopian L. flavopunctatus members [ETHFLAVO]) and the non-Ethiopian ones (non-Ethiopian L. flavopunctatus members [NONETHFLAVO]) in deeply nested relationships. There were distinctly geographically structured mtDNA clades among the NONETHFLAVO, which were incongruous with the nuclear tree where several clades were unresolved. The morphometric datasets did not systematically assign samples to meaningful taxonomic units or agree with the mtDNA clades. The divergence dating and ancestral range reconstructions showed the NONETHFLAVO colonized the current ranges over two independent dispersal events out of Ethiopia in the early Pleistocene. CONCLUSION: The phylogenetic associations and divergence times of the L. flavopunctatus group support the hypothesis that paleoclimatic impacts and ecosystem refugia during the Pleistocene impacted the evolutionary radiation of these rodents. The overlap in craniodental variation between distinct mtDNA clades among the NONETHFLAVO suggests unraveling underlying ecomorphological drivers is key to reconciling taxonomically informative morphological characters. The genus Lophuromys requires a taxonomic reassessment based on extensive genomic evidence to elucidate the patterns and impacts of genetic isolation at clade contact zones.
Keywords: Ethiopia; Phylogeny; mitochondriální DNA; Ecosystem; Integrative systematics; DNA, Mitochondrial; krysa rodu Rattus; zvířata; East Africa; Kivumys; Lophuromys flavopunctatus group; Etiopie; fylogeneze; Bayesova věta; Rats; Animals; Biogeography; Lophuromys; Bayes Theorem; ekosystém